Sosialisasi peran petani dalam pengendalian hama utama tikus di Desa Rappang Barat, Kabupaten Polewali Mandar - Saputra, Muhammad Yusuf; Rasdiana, Rasdiana; Aulia, Riska; St. Nurrahmah; Idris, Idris; Anisa, Anisa; Hasnur, Hasnur; Jannah, Yaumil; Nurpangasi, Aina; Nujriani, Nelia; Fahrianti, Nur Fahra (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2025)
The community of West Rappang Village relies heavily on agricultural yields, particularly rice cultivation. Consequently, pest attacks, especially by rats (Rattus argentiventer), pose a serious threat to food security and farmers' welfare. Conventional control practices, such as the use of rodenticides, have negative impacts on both the environment and human health, and may contribute to pest resistance. The objective of this community service activity is to enhance farmers’ understanding and skills in implementing environmentally friendly Integrated Pest Management (IPM) strategies, while also promoting behavioral change toward sustainable agricultural practices. The methodology employed includes lectures and interactive group discussions conducted in collaboration with farmer partners in West Rappang Village, facilitated by the Unsulbar Farming Club (UFC). The training materials cover ecological rat control techniques, such as the use of bamboo traps, land sanitation, synchronized planting, and the utilization of owls as natural predators. Based on questionnaire results, there was a significant increase in farmers’ knowledge: 100% understood the health risks posed by rat infestations, 88% were aware of pest control information sources, and 100% recognized the importance of environmental cleanliness. This activity demonstrates that participatory and educational approaches can foster collective awareness and empower farmers as agents of change in implementing pest control techniques against rat attacks. The implication of this initiative is the development of a more resilient and sustainable agricultural system, which not only boosts productivity but also improves the overall quality of life for the village community.